2021
DOI: 10.1002/etc.5127
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Drugs in African Surface Waters: Prevalence, Analysis, and Potential Remediation

Abstract: The sources, ecotoxicological impact, and potential remediation strategies of antiretroviral drugs (ARVDs) as emerging contaminants in surface waters are reviewed in this report based on recent literature. The occurrence of ARVDs in water bodies raises concern because many communities in Africa depend on rivers for water resources. Southern Africa is a potential hotspot regarding ARVD contamination due to relatively high therapeutic application and detection thereof in water bodies.Efavirenz and nevirapine are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 126 publications
6
24
0
Order By: Relevance
“…This means that despite the fact that various technologies and prevention methods have been developed, HCWs are still at risk of contracting HIV in their workplaces. This is comparable with the study that was reported from South Africa (4%), 20 Tanzania (3%), 21 and Nigeria (4.2%). 22 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This means that despite the fact that various technologies and prevention methods have been developed, HCWs are still at risk of contracting HIV in their workplaces. This is comparable with the study that was reported from South Africa (4%), 20 Tanzania (3%), 21 and Nigeria (4.2%). 22 …”
Section: Discussionsupporting
confidence: 91%
“…HCWs who were midwives had 4 times higher odds of testing positive for HIV (AOR = 4.2, 95% CI: 3.17, 8.21). This is supported by many studies, such as those in Tunisia, 26 South Africa, 20 and Kenya. 25 The reason could be described as the availability of PPE in healthcare facilities influencing HCWs’ habits of using PPE during patient care and procedures, thereby reducing exposure to HIV and its impact on the outcome of exposure.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, the results indicate a strong dependence of the reaction rate on pH, which emphasizes the significance of pollutant speciation in aqueous solution. Other authors obtained similar results (Adeola and Forbes 2022;Bhembe et al 2020;An et al 2011). To explain the observed trend, it is noteworthy to consider the pKa of the compounds (Table S1) and the PZC of TiO2, which was found to be ≈ 6.0 in our previous work (Ncube et al 2023).…”
Section: The Effect Of Ph On Degradation Kinetics 12supporting
confidence: 69%
“…Despite this, NVP has been found to be highly hazardous, exhibiting potential ecotoxicological effects on sh, algae, and daphnia (Bhembe et al, 2020). Adeola & Forbes, (2022) reported potential ecotoxicity on aquatic fauna while in an earlier study, Archer et al (2017) observed that prolonged exposure to NVP ≤ 1.48mg/l delayed early-stage growth rates in O. mossambicus. It is feared that prolonged exposure may result in viral resistance in humans, particularly people living with HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%